MOLO A'RA SAHU: MARRIAGE CEREMONY OF THE SAHU TRIBE OF WEST HALMAHERA REGENCY - Jainudin Abdullah; Rustam Hasim (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to describe and analyze the meaning, stages, and socio-cultural values contained in the traditional Molo A'ra Sahu marriage ceremony in the Sahu Tribe community in West Halmahera Regency. The research method used is a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation of traditional leaders, community leaders, and couples who carry out the ceremony. The results of the study show that the Molo A'ra Sahu ceremony is not just a marriage procession, but a traditional ritual that is loaded with cultural symbols and values such as mutual cooperation, kinship, responsibility, and respect for ancestors. Each stage of the ceremony — from the proposal (fotu), the handing over of the dowry (molo), to the traditional feast (a'ra) — has a philosophical meaning that reflects the Sahu people's view of the sacredness of the marriage bond and the importance of maintaining social harmony in the community. This study concludes that Molo A'ra Sahu has an important function in preserving local cultural identity and strengthening the social solidarity of the Sahu people in the midst of modernization. It is hoped that the results of this research can be a reference for the preservation of regional culture and learning materials for the younger generation about the local wisdom of West Halmahera.